PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) DENGAN MENGGUNAKAN MEDIA CBC (CUBE BEAM COLOR) - Ri’ayatul Khoiriyah; Ali Shodikin; Heny Ekawati Haryono (INSPIRAMATIKA, 2019)
This research is motivated by students' difficulties in conveying a concept. This is because the role of mathematics as a symbolic language that allows the realization of communication accurately and precisely. The purpose of this research is to find out the difference and which is better between Inside OutsideCircle (IOC) cooperative learning model using CBC media (Cube Beam Color) to improve students' mathematical communication skills on the subject of cubes and beams in class VIII MTs Islamiyah Tulungagung. This research is quantitative research, with this research method Quasy Experimental and research design The Non-Equivalent Control Group Design. The subjects of this study were 46 students consisting of 24 experimental group students and 22 control group students obtained by Cluster Random Sampling technique in class VIII. The instrument was given in the form of a description test consisting of 3 questions and an interview. Based on the results of the study it was concluded that the experimental class was better than the control class. This result can be seen from after the N-gain test is obtained t_table = 2.015> t_count = 31.298, thus is rejected and is accepted. Obtained an average value of learning outcomes has increased for the experimental class of 70.12% in the high category while the control class is 53.43% in the medium category. The results of the t-test statistical analysis pretest obtained result is 0.798> 0.05, which means there is no significant difference between the mathematical communication skills of experimental class students and control class students, whereas the posttest results obtained is 0.003≤0.05, thus, is rejected and is accepted which means there are significant differences in communication skills between the experimental and control classes, it can be concluded that there is a significant difference between the mathematical communication skills taught using the Inside Outside Circle Learning Model using CBC media (Cube Beam Color)with students taught using conversion learning on the subject of cubes and beams.